2017
DOI: 10.1016/j.sdentj.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Oral health comprehension in parents of Saudi cerebral palsy children

Abstract: Parents of CP children generally showed satisfactory oral health comprehension. However, they need further oral health education in several areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 14 publications
(18 reference statements)
4
20
0
1
Order By: Relevance
“…A great number of parents thought that good dental health was important for optimum general health which in line with studies done by Amjad in Saudia [21] and Jyoti Magoo et al in group of Autistic children [22]. Of parents who supervised teeth brushing of their children 80.5% like study done in Brazil [16] and same as study done in group of disabled children in Saudi Arabia [19] because they are partial or total reliance on the caregiver to perform daily activities, such as feeding, mobility and general and oral hygiene.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…A great number of parents thought that good dental health was important for optimum general health which in line with studies done by Amjad in Saudia [21] and Jyoti Magoo et al in group of Autistic children [22]. Of parents who supervised teeth brushing of their children 80.5% like study done in Brazil [16] and same as study done in group of disabled children in Saudi Arabia [19] because they are partial or total reliance on the caregiver to perform daily activities, such as feeding, mobility and general and oral hygiene.…”
Section: Discussionsupporting
confidence: 71%
“…Half of the responded said that they can maintain a good dental health in their children by supervising their tooth brushing, reducing sugary food intake and making regular visits to a dentist; a finding less than that reported by two study done in Saudi Arabia [19,21].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The questionnaire was modified from the one utilized in a previous study. 11 The questionnaire was pre-tested for validity and reliability in 20 parents of CP children not participating in the main study. There was a time interval of 2 weeks for the test-re-test reliability.…”
Section: Methodsmentioning
confidence: 99%
“…[ 14 ] While the study in Riyadh revealed that 51.1% use toothbrush and 1% use miswak as the tooth cleaning aids. [ 15 ] While a study conducted in 2008 among 1115 male students in Al Hasa Saudi Arab reported that 45% were using miswak as a brushing tool. [ 16 ] This might be attributed to either difference in either venues or demographic origin or religious faith in both studies.…”
Section: Discussionmentioning
confidence: 99%